Which patients with metastatic breast cancer benefit from subsequent lines of treatment? An update for clinicians. (November 2013) - Palumbo, Raffaella; Sottotetti, Federico; Riccardi, Alberto; Teragni, Cristina; Pozzi, Emma; Quaquarini, Erica; Tagliaferri, Barbara; Bernardo, Antonio
The outcome of patients with metastatic breast cancer (MBC) has clearly improved over the past decades and the proportion of women living with their disease for several years is increasing. However, the usefulness of multiple lines of treatment is still debated and under evaluation. The available data from both randomized trials and large retrospective series are reviewed and discussed in order to analyze management practices, with emphasis on potential prognostic and predictive factors for clinical outcome. At present, evidence-based medicine provides some support for the use of second-line and to a lesser degree and in selected cases, third-line chemotherapy in human epidermal growth factor receptor 2 (HER2) negative MBC. Beyond third-line treatment, messages from recently reported retrospective studies also suggest a clear potential gain for women receiving further therapies after disease progression, since each line can contribute to a longer survival. In HER2-positive disease, the data from observational and retrospective studies support a clinical benefit from the use of trastuzumab beyond disease progression and emerging evidences from randomized controlled trials are leading to the introduction of newer HER2-targeted therapies in multiple lines. The question 'How many lines of treatment should we give patients?' clearly needs further research through prospective, high-quality clinical trials, aiming for a better definition of factors with prognostic and predictive role. In the meantime, the 'optimal' treatment strategy should probably be to use as many therapeutic options as possible, either in sequence or combination, to keep the best efficacy/toxicity balance, considering MBC as a chronic disease.